Tracing the Jerusalem Code Volume 2: The Chosen People Christian Cultures in Early Modern Scandinavia (1536-ca. 1750) - Oftestad, Eivor Andersen; Haga, Joar (De Gruyter, 2021)
With the aim to write the history of Christianity in Scandinavia with Jerusalem as a lens, this book investigates the image - or rather the imagination - of Jerusalem in the religious, political, and artistic cultures of Scandinavia through most of the second millennium. Jerusalem is conceived as a code, in this volume focussing on Jerusalem's impact on Protestantism and Christianity in Early Modern Scandinavia.